Combination seepage test study of sandy soil and the filter. Issue 10 (30th September 2022) - Cai, Shixing; Fan, Kaifang; Cai, Shizeng; Wang, Zeping; Lin, Jianhong
Abstract: Dams are important structures for the development and utilization of water resources, and dam stability is significantly affected by the filter layer. In this paper, eight groups of combination seepage tests of impermeable materials and filter were conducted. The effects of variations in grade, relative density, and thickness of impermeable materials and filter on the combination seepage resistance performance were assessed. The test results showed that: impermeable material and filter grade significantly affect combination seepage resistance. The critical hydraulic gradient and permeability coefficient decrease by 34% with increasing soil coarseness within the design envelope. The critical hydraulic gradient and failure gradient of specimen decreased by 17 and 20%, when the relative density of the filter material decreased from 0.7 to 0.5, respectively. Therefore, in actual engineering applications, the dry density or relative density of the filter material should be strictly controlled during filling. Increasing the thickness of the filter benefits combination seepage. The effect of changes in particle composition and relative density on the combination seepage characteristics can be expressed by controlling constriction size. HIGHLIGHTS: Impermeability material and filter material combination seepage test were studied. The grading, relative density and thickness of the impermeability and filter material were considered in the test. The relationship of the critical and failure hydraulic gradient with controlling constriction size were studied. Relative density has a significant effect on filtration. Graphical Abstract